IoT-Based Health Monitoring and Tracking System for Self-Quarantine of Covid-19 Patients - Ayup Jehmi @ Ayub, Mohd Nawawi; Zainal Abidin, Zuhairiah (Evolution in Electrical and Electronic Engineering, 2022)
As a result of the global spread of the COVID-19 pandemic, social isolation and quarantine are now globally mandated practices. From this perspective, implementing an Internet of Things (IoT)-based health monitoring and tracking system would be the most effective response to a pandemic. Therefore, this project aims to facilitate early diagnosis and treatment based on the Internet of Things (IoT) technology. A portable health monitoring and tracking system that can monitor basic health factors such as a person’s body temperature, heart rate, and SPO2, as well as their location data, were constructed. Due to the widespread availability of the internet, the system may be remotely monitored at specified intervals using either the online or mobile application. The hardware-based system of the suggested technique employs an Espressif ESP32-WROOM-32 with temperature, Spo2, heart rate and GPS sensors, and the IoT-based method employs the ThingSpeak platform. The proposed system was tested and validated on 10 human subjects and yielded positive results. To verify the efficacy of the sensors, the measured data were compared to the commercial product. It showed approximately maximum relative error between the proposed and the commercial product reading in the measurement of a patient’s body temperature, heart rate, and SPO2 were found to be 2.08%, 1.20%, and 0.69%, respectively. The collected data from the sensors are kept on the ThingSpeak platform at intervals ranging from one second to fifteen seconds. In addition, this project facilitates real-time data collection. A notification system will be triggered when there are any changes to the predetermined standard values of a patient’s health, and then the IoT system will alert the clinician or doctor in line with the patient’s conditions and location. Even if the patient is located in a remote location, a precise diagnosis of their present health is still feasible and limits the risk of disease transmission. In addition, the cloud platform offers data logging, making it easy to review prior collected data and enabling clinicians to diagnose and treat patient health issues promptly.